American Cinema of the 1910s : Themes and Variations - Singer, Ben; Keil, Charlie (Book collections on Project MUSE., 2009)
It was during the teens that filmmaking truly came into its own. Notably, the migration of studios to the West Coast established a connection between moviemaking and the exoticism of Hollywood. The essays in American Cinema of the 1910s explore the rapid developments of the decade that began with D.W. Griffith's unrivaled one-reelers. By mid-decade, multi-reel feature films were profoundly reshaping the industry and deluxe theaters were built to attract the broadest possible audience. Stars like Mary Pickford, Charlie Chaplin, and Douglas Fairbanks became vitally important and companies began.